Efficacy of non-pharmacological treatments in pediatric MASLD: a review of the literature - Mosca, Antonella; Braghini, Maria Rita; Pietrobattista, Andrea; Alisi, Anna; Vania, Andrea (Frontiers in Nutrition, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as non-alcoholic fatty liver disease (NAFLD), comprises a spectrum of liver disorders characterized by excessive accumulation of triglycerides in hepatocytes. There are multiple treatment strategies proposed for pediatric MASLD, with lifestyle modifications and a balanced dietary regimen – particularly the Mediterranean diet in combination with weight loss, when needed – currently representing the cornerstone of clinical management. Behavioral psychological interventions are gaining increasing importance particularly in addressing comorbid eating disorders and supporting long-term adherence to therapeutic regimens. In addition, in daily clinical practice, the use of food supplements with antioxidant and hepatocyte anti-inflammatory effects is indicated in more advanced stages of steatosis, with the aim of limiting disease progression toward high-grade fibrosis and/or cirrhosis. This review aims to summarize current behavioral and nutritional therapeutic approaches for the management of pediatric MASLD.